Calloselasma rhodostoma Envenomation in An Indonesian Pregnant Woman: A Rare Case Report - Mahrus, Mahrus; Zainayah, Munsifah; Abdullah, Taufiq; Haedar, Ali; Maharani, Tri; Azizah, Maghfira Rahma; Khairunnisa, Naila Nurhana; Octavandi, Rafliandy Achmad; Aryanto, Zaki Yuli (Jurnal Kedokteran Brawijaya, 2026)
Despite their relatively frequent occurrence, snakebite incidents in Indonesia are often underreported. Calloselasma rhodostoma, a hemotoxic snake, can cause coagulopathy and severe bleeding. Envenomation during pregnancy is rare but poses significant risks to both mother and fetus. We report a case of a 34-year-old woman in her second trimester who sustained a bite on her lower right leg. She presented within two hours with local pain, swelling, and gingival bleeding, indicating early systemic involvement. Laboratory findings confirmed severe thrombocytopenia (2,000/µL). Prompt management with immobilization and antivenom therapy was initiated. Following treatment, platelet counts improved significantly to 84,000/µL after the first dose and 176,000/µL after the second dose, without any obstetric complications. Early administration of antivenom effectively reversed coagulopathy and prevented maternal and fetal adverse outcomes. This case highlights the importance of timely intervention in hemotoxic snakebite during pregnancy and demonstrates favorable maternal and fetal outcomes with appropriate management.